Linkage Map Development by EST-SSR Markers and QTL Analysis for Inflorescence and Leaf Traits in Chrysanthemum (Chrysanthemum morifolium Ramat.) - Min Fan; Yike Gao; Zhiping Wu; Qixiang Zhang (Plants, 2020)
Chrysanthemums (Chrysanthemum morifolium Ramat.) are famous ornamental crops with high medicinal and industrial values. The inflorescence and leaf traits are key factors that affect the yield and quality of chrysanthemum. However, the genetic improvement of those traits is slow within chrysanthemum because of its hexaploidy, high heterozygosity and enormous genome. To study the genetic control of the important traits and facilitate marker-assisted selection (MAS) in chrysanthemum, it is desirable to populate the genetic maps with an abundance of transferrable markers such as microsatellites (SSRs). A genetic map was constructed with expressed sequence tag–simple sequence repeat (EST-SSR) markers in an F1 progeny of 192 offspring. A total of 1000 alleles were generated from 223 EST-SSR primer pairs. The preliminary maternal and paternal maps consisted of 265 marker alleles arranged into 49 and 53 linkage groups (LGs), respectively. The recombined parental maps covered 906.3 and 970.1 cM of the genome, respectively. Finally, 264 polymorphic loci were allocated to nine LGs. The integrated map spanned 954.5 cM in length with an average genetic distance of 3.6 cM between two neighbouring loci. Quantitative trait loci (QTLs) analysis was performed using the integrated map for inflorescence diameter (ID), central disc flower diameter (CDFD), number of whorls of ray florets (NWRF), number of ray florets (NRF), number of disc florets (NDF), number of florets (NF), ray floret length (RFL), ray floret width (RFW), ray floret length/width (RFL/W), leaf length (LL), leaf width (LW) and leaf length/width (LL/W). Overall, 36 (21 major) QTLs were identified. The successful mapping of inflorescence and leaf traits QTL demonstrated the utility of the new integrated linkage map. This study is the first report of a genetic map based on EST-SSR markers in chrysanthemum. The EST-SSR markers, genetic map and QTLs reported here could be valuable resources in implementing MAS for chrysanthemums in breeding programs.